The securities markets : operations and issues - Robbins, Sidney M. (New York : Free Press, 1966)
The book covers both the legal and economic aspects of the stock market and brings out the interrelationships among them. The author also gave his personal evaluation.
Includes bibliographical references: p. 287-293 and index.
oif 28/01/2019
Loans
Keywords: Securities; Stock exchanges